2020
DOI: 10.3390/catal10010081
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Biocatalytic Performance of Nanofiber-Supported β-Galactosidase for Production of Galacto-Oligosaccharides

Abstract: Molecular distribution, structural conformation and catalytic activity at the interface between enzyme and its immobilising support are vital in the enzymatic reactions for producing bioproducts. In this study, a nanobiocatalyst assembly, β-galactosidase immobilized on chemically modified electrospun polystyrene nanofibers (PSNF), was synthesized for converting lactose into galacto-oligosaccharides (GOS). Characterization results using scanning electron microscopy (SEM) and fluorescence analysis of fluorescein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…A direct comparison with literature data is not possible, but in a study that was performed in a continuous packed bed reactor with β-galactosidase immobilized on double-layered hydrophilic polymer-coated magnetic nanoparticles, 100% conversion was achieved [15]. Comparison of lactose bioconversion has shown that in different reactors using different support materials for β-galactosidase immobilization, lactose conversion rates were between 38% and 88% [33].…”
Section: Hydrolysis Of Lactosementioning
confidence: 99%
See 1 more Smart Citation
“…A direct comparison with literature data is not possible, but in a study that was performed in a continuous packed bed reactor with β-galactosidase immobilized on double-layered hydrophilic polymer-coated magnetic nanoparticles, 100% conversion was achieved [15]. Comparison of lactose bioconversion has shown that in different reactors using different support materials for β-galactosidase immobilization, lactose conversion rates were between 38% and 88% [33].…”
Section: Hydrolysis Of Lactosementioning
confidence: 99%
“…Catalysts 2023, 13, x FOR PEER REVIEW 7 of 12 using different support materials for β-galactosidase immobilization, lactose conversion rates were between 38% and 88% [33].…”
Section: Hydrolysis Of Lactosementioning
confidence: 99%
“…Electrospinning is applied as a versatile, potentially high throughput, and powerful means of continuously preparing desirable fibrous membranes, which are considered good carriers for enzyme immobilization because of their high porosity, interconnectivity, and variable spinning materials. Notably, the nanofiber membranes can retain their morphological structures well through hydrolysis and can be surface functionalized with stimuli-responsive polymer chains (Figure ).…”
Section: Strategies For Generating Sr-ppmsmentioning
confidence: 99%
“…Fathi et al (2022) reported that substrate concentration, temperature and pH could influence enzyme activity. β-galactosidase, an enzyme of significant industrial importance, has attracted attention in the industry for its pivotal role in catalyzing the breakdown of lactose molecules, leading to the creation of enzyme-galactosyl ISSN (print): 1823-8262, ISSN (online): 2231-7538 complexes (Misson et al, 2020). These complexes then proceed down either the hydrolysis or transgalactosylation pathways.…”
Section: Introductionmentioning
confidence: 99%